TINJAUAN FIQH MUAMALAH TERHADAP SYIRKAH BAGI HASIL USAHA AKI UD. PRIBAWA - Husaini, Afrida; Khoirul Anwar, Moch (Universitas Negeri Surabaya, 2022)
Syirkah is a partnership with the enactment of the right to something for two or more parties with the aim of the partnership to run a business or business, both in the field of trade or services where the provision of capital can come from any allied party or from one of them. Activities of running capital can be carried out by all parties involved, or some of the parties who share. Likewise with the distribution of profits that will be divided according to the applicable agreement. This study aims to determine the application of UD syirkah. Pride, and to find out from the perspective of fiqh muamalah regarding the application of syirkah at UD. priviledge. Previously UD. Pribawa is a trading business which is engaged in the sale and purchase of batteries for motor vehicles which is run by three brothers. This research uses descriptive qualitative method. To collect data this technique uses interviews, observation, and documentation. The results of this study indicate that the syirkah system used at UD. Pribawa is using syirkah inan. In addition, at UD. Pribawa has carried out the renewal of syirkah cooperation, because two of the three shareholders/capital owners have died.